Mitochondrial Medicine: A Promising Therapeutic Option Against Various Neurodegenerative Disorders - Almikhlafi, Mohannad A.; Karami, Mohammed M.; Jana, Ankit; Alqurashi, Thamer M.; Majrashi, Mohammed; Alghamdi, Badrah S.; Ashraf, Ghulam Md. (Current Neuropharmacology, 2023)
Abnormal mitochondrial morphology and metabolic dysfunction have been observed in many neurodegenerative disorders (NDDs). Mitochondrial dysfunction can be caused by aberrant mitochondrial DNA, mutant nuclear proteins that interact with mitochondria directly or indirectly, or for unknown reasons. Since mitochondria play a significant role in neurodegeneration, mitochondriatargeted therapies represent a prosperous direction for the development of novel drug compounds that can be used to treat NDDs. This review gives a brief description of how mitochondrial abnormalities lead to various NDDs such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis. We further explore the promising therapeutic effectiveness of mitochondria- directed antioxidants, MitoQ, MitoVitE, MitoPBN, and dimebon. We have also discussed the possibility of mitochondrial gene therapy as a therapeutic option for these NDDs.
Keywords: amyotrophic lateral sclerosis